MITRAL ANNULAR CALCIFICATION IN STAGE 5 CHRONIC KIDNEY DISEASE ON DIALYSIS THERAPY - Mansur, Abeera; Saleem, Sidra; Naveed, Haris; Ittefaq, Afshan; Mahmood, Asad; Sarwar, Shahbaz (Journal of Ayub Medical College Abbottabad, 2020)
Background: Mitral Annular Calcification (MAC) is a degenerative process involving the mitral valve and is a marker of advanced cardiovascular disease. Prevalence in the general population is upto 10% and increases in advanced age, diabetes mellitus, chronic kidney disease (CKD), end stage renal disease (upto 40%) and mitral valve prolapse.The aims of this study were to assess the prevalence of MAC in CKD5D patients and correlate with patients' characteristics. Methods: Echocardiograms were obtained in 84 hemodialysis patients. Association of MAC with various patient characteristics was studied. Data was analysed using SPSS-22. Results: The mean age of the patients was 63.38±12.3 years and 48 (57%) were males. Sixty-eight patients (81%) had DM and 79 (94%) had hypertension. MAC was present in 37 out of 84 (44%) patients. Sixty-four (72%) had IHD. The presence of MAC correlated significantly with IHD (Odds Ratio 6.42, p=0.006). Mean follow up of the patients was 30.30±29.22 months and 37 (44%) suffered mortality during this period. Patients on dialysis for longer than 36 months had an elevated risk of developing MAC (OR=3.32, p=0.019). Patients with the following risk factors: serum PO4 greater than 5.5 (OR=2.03), DM (OR=1.95), HTN (OR=3.35), Age >60 (OR=1.83), AFIB (OR=1.28); had an observable increase in incidence of MAC with time but they weren't statistically significant. Conclusion: Mitral Annular Calcification is common in hemodialysis patients and correlates significantly with IHD. Our findings support the recommendation by KDIGO 2017 guidelines on Mineral and Bone Disease on the use of echocardiography for the detection of valvular calcification. Keywords: Chronic Kidney Disease; Cardiovascular disease; Mitral Value; Annular calcification